2011
DOI: 10.1152/ajpcell.00493.2010
|View full text |Cite
|
Sign up to set email alerts
|

Obligatory role of heat shock protein 90 in iNOS induction

Abstract: Luo S, Wang T, Qin H, Lei H, Xia Y. Obligatory role of heat shock protein 90 in iNOS induction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 29 publications
(49 reference statements)
1
22
0
Order By: Relevance
“…5). Additionally, previous studies demonstrated that HSP90 inhibitors similarly induced anti-oxidative [42], [43], [44], [45] and anti-inflammatory responses in in vivo and in vitro infection models not involving Leishmania [46], [47], [48]. Taken together, these findings directly contradict the literature, which clearly evidences the production of proinflammatory mediators TNF-α, IL-1β, IL-6, IL-12, IFN-γ and MCP-1 being associated with the control of Leishmania spp infection [40], [49], [50], [51].…”
Section: Discussionmentioning
confidence: 88%
“…5). Additionally, previous studies demonstrated that HSP90 inhibitors similarly induced anti-oxidative [42], [43], [44], [45] and anti-inflammatory responses in in vivo and in vitro infection models not involving Leishmania [46], [47], [48]. Taken together, these findings directly contradict the literature, which clearly evidences the production of proinflammatory mediators TNF-α, IL-1β, IL-6, IL-12, IFN-γ and MCP-1 being associated with the control of Leishmania spp infection [40], [49], [50], [51].…”
Section: Discussionmentioning
confidence: 88%
“…The fact that different pathways are involved in calcium influx and TNF-a and NO production reinforces that gedunin blocks an upstream and common mechanism involved in these three responses, most likely due to MD-2 binding. However, the modulation of Hsp90 by gedunin (Brandt et al, 2008;Patwardhan et al, 2013) also explains the impairment of LPSinduced NO production, since NO synthesis has been shown to be modulated by Hsp90, through Hsp90-inducible nitric oxide synthase interaction (Yoshida and Xia, 2003;Luo et al, 2011). Indeed, it was previously reported that Hsp90 inhibition by geldanamycin also impaired NO production by macrophages stimulated with LPS (Luo et al, 2011).…”
Section: Discussionmentioning
confidence: 98%
“…For example, PES was found to possess anti-leukemic actions in human primary AML blasts [9]. Repression of Hsp90 activity prevents LPS-induced iNOS expression [39] and liver injury [21]. More importantly, one of the Hsp70 ATPase inhibitors, methylene blue, has also entered phase III trials to treat Alzhaimer’s disease patients [40].…”
Section: Discussionmentioning
confidence: 99%